Influence of infill parameters on the tensile strength of ABS 3D printing filament - Winsen, L.; Michel, J.; Putra, W.M.; Lubis, S.Y.; Siahaan, E. (Dinamika Teknik Mesin, 2025)
This study aims to analyze the effect of infill parameters on the tensile strength of Acrylonitrile Butadiene Styrene (ABS) filament in the 3D printing process for the manufacture of prototype cat prosthetics. ABS filament was chosen because it has good mechanical strength, resistance to high temperatures, and the ability to be further processed after printing. The infill parameters studied include infill percentage, layer thickness, and print speed. The research methodology involved making test samples with varying infill percentages, which were then tested using a tensile testing machine to measure the maximum tensile strength. The infill percentage was varied between 25%, 50%, 80%, and 100%. Tensile strength testing was conducted in accordance with ASTM D638 standards to determine the mechanical characteristics of the molded specimens and then the optimal infill parameters were applied in the design and manufacture of the cat prosthetic leg prototype, ensuring better load distribution and higher durability. The results show that the percentage density of infill has a positive correlation with the tensile strength of the specimen; an increase in infill density increases the tensile strength of the material. The findings provide practical guidance in the selection of infill parameters for tensile strength optimization in 3D printing applications using ABS filament so that it can be known that the influence of infill parameters greatly affects the strength of manufacturing.